Synthesis of Zn(InxGa1-x)2O4 solid-solutions with tunable band-gaps for enhanced photocatalytic hydrogen evolution under solar-light irradiation. (28th February 2020) - Li, Qiaoqi; Zhang, Lili; Tang, Chao; Zhao, Pusu; Yin, Chengzhu; Yin, Jingzhou
Abstract: The systematic investigation of In 3+ ions doped ZnGa2 O4 applying to photocatalytic H2 evolution (PHE) under simulated solar-light irradiation was first reported here. A series of Zn(In x Ga1- x )2 O4 ( x  = 0 to 0.4) solid-solutions were obtained by sol-gel method and characterized by XRD, SEM, elemental mapping, XPS, UV–Vis DRS and N2 adsorption measures. The concentration of In 3+ ions remarkably enhanced the light-harvesting capability of Zn(In x Ga1- x )2 O4 solid-solutions in the visible-light region, and successfully regulated the positions of the CB-bottom potential, ultimately improving the photocatalytic capabilities under simulated solar-light irradiation. Among composites containing different In 3+ ions dosages, Zn(In0.1 Ga0.9 )2 O4 demonstrated the most excellent photocatalytic capability for solar-light-driven PHE reaction (H2 : 240.6  μ mol/h/g), in which the stability of the Zn(In0.1 Ga0.9 )2 O4 was confirmed by several techniques. Graphical abstract: Image 1 Highlights: First study on Zn(In x Ga1- x )2 O4 for photocatalytic hydrogen evolution driven by simulated solar-light. The band-gaps and CB-bottom potentials of Zn(In x Ga1- x )2 O4 could be adjusted by the doping content of In 3+ ions. The optimum content of In 3+ ensures the maximum photocatalytic capability of ZnIn0.1 Ga1.9 O4 under simulated solar-light.